2008
DOI: 10.1093/jnci/djn066
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Group-Randomized Trials in Cancer: A Review of Current Practices

Abstract: Many investigators who use group-randomized trials in cancer research do not adequately attend to the special design and analytic challenges associated with these trials. Failure to do so can lead to reporting type I errors as real effects, mislead investigators and policy-makers, and slow progress toward control and prevention of cancer. A collaborative effort by investigators, statisticians, and others will be required to ensure that group-randomized trials are planned and analyzed using appropriate methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 112 publications
0
78
1
2
Order By: Relevance
“…Proportions of trials in which clustering was accounted for in the sample size and analysis (Table 4) were similar to those for cluster randomised trials in all fields [12], and in the fields of tropical disease and oncology [11,38], but lower than in other areas [4,24,27]. Relative to previous reviews, we judged that identification/recruitment bias was possible in a lower percentage (7%) and unclear in a higher percentage (32%) of our included trials [4,27].…”
Section: Discussionmentioning
confidence: 85%
“…Proportions of trials in which clustering was accounted for in the sample size and analysis (Table 4) were similar to those for cluster randomised trials in all fields [12], and in the fields of tropical disease and oncology [11,38], but lower than in other areas [4,24,27]. Relative to previous reviews, we judged that identification/recruitment bias was possible in a lower percentage (7%) and unclear in a higher percentage (32%) of our included trials [4,27].…”
Section: Discussionmentioning
confidence: 85%
“…[35][36][37][38][39][40][41][42] For example, the unit of analysis error (where results were analysed without accounting for the clustering) was seen in 19/40 (48%) of medical care trials, 35 and among 75 reports of cluster trials in cancer prevention and control a third (34%) "failed to report any analyses that were judged to be appropriate." 37 Among 50 reports of cluster trials of screening interventions, 32 (64%) reported using a method of analysis that took account of clustering, but in several the method used was not stated explicitly.…”
Section: Discussionmentioning
confidence: 99%
“…Group-Randomized Trials (GRTs) are widely used for comparative studies when randomization at the individual level is not possible without substantial risk of contamination [1]. In a GRT, groups of subjects (e.g., schools, clinics, communities) are randomized to study groups, while outcomes are measured at the individual level.…”
Section: Introductionmentioning
confidence: 99%
“…Both GRTs and IRGT trials are commonly used study designs for intervention research and are employed across a range of disciplines [1, 4, 5]. There is a vast literature on the design and analysis of GRTs [2, 3], while there are far fewer publications on the methodologic challenges of IRGT trials [e.g., 6, 7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%